2023
DOI: 10.3390/nu15041013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Interventions of Exercise and Diet or Exercise and Supplementation on Breast Cancer Patients: A Systematic Review

Abstract: This systematic review investigated the effects of exercise interventions combined with diet and/or dietary supplement interventions on anthropometry, body composition, metabolic biomarkers, physical function, healthy lifestyles, quality of life, psychosocial variables and fatigue for women with breast cancer. A systematic search was performed in the PubMed and Web of Science databases (from inception to 1 March 2022). A review was carried out following the Preferred Reporting Items for Systematic review and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…Nevertheless, lifestyle and nutrition has changed within the last 30 years, which could also be a possible explanation for this difference. A recent systematic review indicated the importance of exercise interventions as well as supplement interventions (e.g., vitamin D) in breast cancer patients, and their positive effects on cardiorespiratory fitness, body composition, and quality of life [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, lifestyle and nutrition has changed within the last 30 years, which could also be a possible explanation for this difference. A recent systematic review indicated the importance of exercise interventions as well as supplement interventions (e.g., vitamin D) in breast cancer patients, and their positive effects on cardiorespiratory fitness, body composition, and quality of life [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search was conducted in the aforementioned databases to scrutinize eligible trials. Additionally, the reference lists of various review articles [ 5 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] were examined and manual searches were performed. In situations where the two initial reviewers were unable to reach a consensus, a third reviewer and study author (PLC) was consulted.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with control groups, groups who performed interventions that combine exercise and diet demonstrate significant improvements in cardiorespiratory fitness, muscle strength, body composition, quality of life, fatigue, anxiety, depression, and sleep. Conversely, exercise combined with supplementation does not result in an improvement over exercise alone or supplementation alone [ 171 ].…”
Section: Modulation Of the Microbiota Through Diet As A Potential Adj...mentioning
confidence: 99%